2011
DOI: 10.1007/s12070-011-0306-7
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage–Perichondrium: An Ideal Graft Material?

Abstract: Temporalis fascia has long been regarded as the ideal graft material for tympanic membrane repair. However it often does not seem to withstand negative middle ear pressure in the post operative period. Tragal cartilage with perichondrium would appear to be a better graft material with good hearing outcome. It can be obtained easily with cosmetically acceptable incision. In the present study, we have compared the graft properties of temporalis fascia verses tragal cartilage perichondrium with respect to healing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 29 publications
2
46
0
Order By: Relevance
“…11 However, cartilage graft is characterized by its resistance to resorption, retraction and negative pressure in middle ear. …”
Section: Resultsmentioning
confidence: 99%
“…11 However, cartilage graft is characterized by its resistance to resorption, retraction and negative pressure in middle ear. …”
Section: Resultsmentioning
confidence: 99%
“…For example, in a study performed by Chhapola et al the rate of perforation in temporalis muscle fascia grafts at 6. months was 4.2 %, while at 2 year controls, it increased 2-fold up to 9.85 % [18]. In the same study, rates of perforation in the cartilage graft at 6 month and 1-year controls did not change.…”
Section: Discussionmentioning
confidence: 64%
“…Postoperative healing, rate of retraction and re-perforation was compared for both materials. The results in this study indicated that composite graft had an edge over TF in terms of graft take up rates and hearing gain [39]. Another article was published by Shetty S which aimed at finding the post operative hearing improvement in patients having COM with pure conductive hearing loss, using different type of tympanoplasties.…”
Section: Experiments With Cartilage and Perichondriummentioning
confidence: 71%